Correction: Evaluation of Schistosome Promoter Expression for Transgenesis and Genetic Analysis. - Shuang Liang; Melissa Varrecchia; Kenji Ishida; Emmitt R Jolly (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0098302.].